Aquatic fungi and fish production in Egypt: II - in vivo studies - Abdel hamid, A.M.; Shabana, Y.M.; Gomaa, Sahar S.A. (2009)
Out of the present study, it can be concluded that Trichodenna viride is a promising biocontrol agent for the fish pathogens, Saprolegnia sp. and Aspergillus ochraceus. It can be easily cultured and its inoculum can survive in water and significantly reduce saprolegniasis severity on the Nile tilapia fish. The fungus T. viride is safe and is also used for biological control purposes against plant pathogens. It can also be concluded that the fungus Alternaria eichhorniae (Ae5) which did not cause any mortality to the treated fish can be safely used for the biocontrol of water hyacinth with no negative effects on fish.
Includes reference.
Summary in Arabic.
1
Keywords: Nile tilapia -- Diseases; Fishes -- Diseases; Trichoderma; Aquatic fungi -- Control; Fish Productions